Low L3 skeletal muscle index and endometrial cancer: a statistic pooling analysis - Na Aru; Congyu Yang; Yuntian Chen; Jiaming Liu (BMC Cancer)
Abstract Objective Sarcopenia, a condition characterized by the gradual decline of muscle mass, strength, and function, is a key indicator of malnutrition in cancer patients and has been linked to poor prognoses in oncology. Sarcopenia is commonly assessed by measuring the skeletal muscle index (SMI) of the third lumbar spine (L3) using computed tomography (CT). This meta-analysis aimed to explore the relationship between low SMI and clinicopathological features, as well as prognosis, in individuals with endometrial cancer (EC). Methods Data from various databases including PubMed, Embase, Cochrane, Medline, and Web of Science were searched up until October 20th, 2024. Studies that investigated the association of low SMI and EC survival or clinicopathological characteristics were included. Pooled effect sizes were reported as hazards ratio (HR), odds ratios (ORs) or weighted mean difference (WMD). The quality and risk of bias in the studies were evaluated using the Newcastle-Ottawa Scale (NOS) and the Quality In Prognosis Studies (QUIPS), and the study was registered on PROSPERO (CRD42024509949) before commencing the search. Results A total of 218 studies were identified across all five databases, with 11 studies meeting the criteria for qualitative and quantitative analysis, involving 1588 patients. The findings of our meta-analysis demonstrated a significant link between low SMI and progression-free survival [P = 0.002; HR: 1.62, 95% CI: 1.20–2.17]. Low SMI was also associated with a BMI < 25 (P < 0.00001; OR: 4.55, 95% CI: 3.01–6.87), FIGO stage (P = 0.04; OR: 1.33, 95% CI: 1.01–1.75), pathology grades (P = 0.001; OR: 1.77, 95% CI: 1.26–2.49), and the endometrioid pathological type (P = 0.01; OR: 0.68, 95% CI: 0.51–0.92). However, no significant correlation was found between low SMI and 5-year overall survival, serous pathological type, recurrence, length of hospital stay, intraoperative complications, and postoperative complications. All the included studies scored ≥ 7 on the NOS, indicating relatively high-quality evidence. Conclusions The meta-analysis highlighted the association between low SMI and unfavorable clinical features and outcomes in EC patients, emphasizing the importance of early diagnosis and appropriate management of sarcopenia assessed by low SMI to enhance prognoses in EC patients.